Endoscopic Treatment for Pediatric Esophageal Stenosis Induced by Chemical Burn, Congenitally, or After Surgical Repair of Esophageal Atresia - Bingyi Zhou; Bingyi Zhou; Hailing Peng; Hailing Peng; Liu Han; Liu Han; Chengbai Liang; Chengbai Liang; Liang Lv; Liang Lv; Xuehong Wang; Xuehong Wang; et al. (Frontiers in Pediatrics, 2022)
ObjectivesTo evaluate the safety and efficacy of endoscopic treatment for congenital pediatric esophageal stenosis or pediatric stenosis that develops after a chemical burn or surgical repair of esophageal atresia.MethodsWe retrospectively reviewed the medical records of 15 pediatric patients who underwent endoscopic treatments (dilation and/or stenting and/or incision) for congenital esophageal stenosis or esophageal stenosis that developed after a chemical burn or surgical repair of esophageal atresia, between January 2010 and January 2019. The patients were periodically followed-up to assess the safety and efficacy of treatment by comparing the diameter of stricture and dysphagia score before and after procedures, and complications or recurrence.ResultsAll children successfully underwent the procedures. Fourteen of the 15 patients received endoscopic balloon dilation (EBD) as the first step of treatment, but EBD alone only resolved the symptoms in two patients. The remaining patients received other comprehensive treatments, such as EBD with endoscopic incision (EI), EBD with stent replacement, or a combination of EBD, stent replacement, and EI. Eleven (11/15, 73.3%) patients experienced symptomatic relief after endoscopic treatment, and recurrence was noted in four patients on 3–36 months after the final endoscopic treatment. All four patients underwent esophageal surgery to relieve their symptoms. Until October 2021, all patients experienced symptom relief, and their dysphagia scores decreased from 3–4 to 0–1 during the follow-up period of 8–121 months. The average diameter of stenosis was increased from 0.34 cm (range 0.2–0.7 cm) to 1.03 cm (range 0.8–1.2 cm). No severe complications occurred during endoscopic treatment and follow-up.ConclusionsEndoscopic treatment is safe and effective for pediatric esophageal stenosis that is congenital or induced by chemical burns or surgical repair of esophageal atresia. Comparative large-scale studies are required to confirm our findings.